2021
DOI: 10.1038/s42003-021-01662-9
|View full text |Cite
|
Sign up to set email alerts
|

A hypomorphic variant in EYS detected by genome-wide association study contributes toward retinitis pigmentosa

Abstract: The genetic basis of Japanese autosomal recessive retinitis pigmentosa (ARRP) remains largely unknown. Herein, we applied a 2-step genome-wide association study (GWAS) in 640 Japanese patients. Meta-GWAS identified three independent peaks at P < 5.0 × 10−8, all within the major ARRP gene EYS. Two of the three were each in linkage disequilibrium with a different low frequency variant (allele frequency < 0.05); a known founder Mendelian mutation (c.4957dupA, p.S1653Kfs*2) and a non-synonymous variant (c.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…Also, carrier frequencies of homozygous (4.13 × 10 −3 , 5/1210) and compound heterozygous (2.23 × 10 −2 , 27/1210) p.G843E in our IRD cohort were significantly higher than their expected frequencies in the general Japanese population (homozygous p.G843E: 3.57 × 10 −4 by 8.3KJPN, p = 8.73 × 10 −5 ; compound heterozygous p.G843E: 1.38 × 10 −4 by 8.3KJPN, p < 2.2 × 10 −16 ) (Supporting Information: Table ). Together with previous reports showing p.G843E variant enrichment in Japanese RP patients (Nishiguchi et al, 2021; Numa et al, 2020), and functional data showing a reduced rescue efficiency of a p.G843E mutant construct in zebrafish (Nishiguchi et al, 2021), our data suggested that p.G843E may contribute to the IRD phenotype either in trans with other EYS mutations or as a homozygous variant. Therefore, we propose that the p.G843E variant is pathogenic.…”
Section: Discussionsupporting
confidence: 88%
“…Also, carrier frequencies of homozygous (4.13 × 10 −3 , 5/1210) and compound heterozygous (2.23 × 10 −2 , 27/1210) p.G843E in our IRD cohort were significantly higher than their expected frequencies in the general Japanese population (homozygous p.G843E: 3.57 × 10 −4 by 8.3KJPN, p = 8.73 × 10 −5 ; compound heterozygous p.G843E: 1.38 × 10 −4 by 8.3KJPN, p < 2.2 × 10 −16 ) (Supporting Information: Table ). Together with previous reports showing p.G843E variant enrichment in Japanese RP patients (Nishiguchi et al, 2021; Numa et al, 2020), and functional data showing a reduced rescue efficiency of a p.G843E mutant construct in zebrafish (Nishiguchi et al, 2021), our data suggested that p.G843E may contribute to the IRD phenotype either in trans with other EYS mutations or as a homozygous variant. Therefore, we propose that the p.G843E variant is pathogenic.…”
Section: Discussionsupporting
confidence: 88%
“…Our cohort, and those reported elsewhere, 14–20 may represent the more severe end of the disease spectrum that involves C2139Y. Hypomorphic EYS alleles have been reported in a Japanese RP cohort recently, 27 and their high population frequency makes it likely that they do not cause clinical disease when present homozygously. The C2139Y variant does appear to cause clinically relevant disease homozygously, and thus it should not be considered hypomorphic.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, it is an urgent global issue to develop a strategy to delay progressive retinal dystrophy. Although gene therapy has been reported to be safe and effective for one type of inherited retinal dystrophy [ 10 13 ], and several drugs are promising [ 14 – 17 ], no established treatments are available for EYS-RP to date.…”
Section: Introductionmentioning
confidence: 99%